1998
DOI: 10.1063/1.122754
|View full text |Cite
|
Sign up to set email alerts
|

A method for liquid crystal alignment using in situ ultraviolet exposure during imidization of polyimide

Abstract: Homogeneous alignment of liquid crystals can be achieved by a technique using polyimide films and in situ exposure to linearly polarized ultraviolet (LPUV) light during imidization. The alignment layers prepared by this method exhibit higher thermal stability while requiring shorter processing time than the conventional UV alignment method which employs UV exposure after the imidization of polyimide is complete. Multidomain cells can be easily fabricated with the use of a photomask and multistep in situ LPUV e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…This photoalignment method is still studied actively, [9][10][11][12][13][14] but photodecomposition may cause lowering of the inherent stability of polyimide films. [15][16][17] On the other hand, Park et al reported an alignment method based on the photoisomerization reaction of polyamic acid containing azobenzene in the backbone structure ͑azo-PAA͒. 18 Since this method contains no decomposition reaction of polyimide, the inherent stability of the polyimide film is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…This photoalignment method is still studied actively, [9][10][11][12][13][14] but photodecomposition may cause lowering of the inherent stability of polyimide films. [15][16][17] On the other hand, Park et al reported an alignment method based on the photoisomerization reaction of polyamic acid containing azobenzene in the backbone structure ͑azo-PAA͒. 18 Since this method contains no decomposition reaction of polyimide, the inherent stability of the polyimide film is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…The targets of these reactions are normally aromatic fragments of main or side polymer chains. Apart from PIs [17,93,97,98], polysilanes [99,100], polystyrene, polyesters and some other aromatic polymers [101] undergo photoalignment upon photodestruction. Photodestroyable PIs usually have a sufficiently high anchoring energy of 10 −5 J/m 2 [102,103].…”
Section: Photo-degradation In Polyimide Filmsmentioning
confidence: 99%
“…Many researchers have reported a rubbing-free method for LC alignment [13][14][15][16]. Most recently, the LC alignment and pretilt angle generation using the in-situ photoalignment method on a PI surface for homogeneous alignment have been reported [17]. The in-situ photoalignment method produces a higher thermal stability of LC alignment than that produced using the conventional photoalignment method.…”
Section: Introductionmentioning
confidence: 99%